1998
DOI: 10.1016/s0014-5793(98)01250-2
|View full text |Cite
|
Sign up to set email alerts
|

(−)‐2C‐Methyl‐d‐erythrono‐1,4‐lactone is formed after application of the terpenoid precursor 1‐deoxy‐d‐xylulose

Abstract: Application of [1,2-14 C]1-deoxy-D-xylulose, the committed precursor of terpenoids, thiamine and pyridoxol, to a variety of plant species resulted in the labelling of an unknown metabolite. The isolation and purification of this metabolite from Ipomoea purpurea plants fed with 1-deoxy-D-xylulose (DX), followed by NMR analysis, resulted in the identification of its structure as (3)-2C-methyl-D-erythrono-1,4-lactone (MDEL). MDEL has been previously isolated as a stress metabolite of certain plants. A hypothetica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The uniqueness of the epimerization reaction described herein assumes further significance when the close correspondence is noted between the Mo-catalyzed interconversion of 9 and 2 and the proposed metabolism of 1 via the non-mevalonate isoprenoid pathway. It has been suggested that 1 is converted in vivo to 2- C -(methyl)- d -erythritol 4P via tandem pinacol rearrangement/reduction during its metabolism. The molybdate-catalyzed rearrangement described herein mimics this biological transformation. In the metabolic pathway, no evidence exists implicating the involvement of molybdenum in the pinacol rearrangement.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…The uniqueness of the epimerization reaction described herein assumes further significance when the close correspondence is noted between the Mo-catalyzed interconversion of 9 and 2 and the proposed metabolism of 1 via the non-mevalonate isoprenoid pathway. It has been suggested that 1 is converted in vivo to 2- C -(methyl)- d -erythritol 4P via tandem pinacol rearrangement/reduction during its metabolism. The molybdate-catalyzed rearrangement described herein mimics this biological transformation. In the metabolic pathway, no evidence exists implicating the involvement of molybdenum in the pinacol rearrangement.…”
mentioning
confidence: 84%
“…In most eukaryotic organisms and archaebacteria, the mevalonate pathway is responsible for the biosynthesis of isoprenoid compounds wherein acetyl CoA serves as the metabolic precursor. Recent studies, however, suggest that 1-deoxy- d -xylulose 5-phosphate 1 serves as a precursor in the biosynthesis of isoprenoids in bacteria, green algae, and plants, as well as in the biosynthesis of vitamins B 6 and B 1 . Interest in elucidating these new pathways has stimulated recent reports on the preparation of 1-deoxy- d -xylulose 2 and its 5-phosphate 1 . Here we describe a chemical route to 2 (Scheme 1) involving a unique carbon skeleton rearrangement that mimics one of the putative metabolic reactions of these pathways.
…”
mentioning
confidence: 96%
“…The feeding of labelled deoxyxylulose to Ipomoea purpurea plants leads to formation of a metabolite, identified as 2-C-methyl--erythrono-1,4-lactone 20. 51 Similar transformation occurs in a variety of plant systems. This compound had previously been isolated as a stress metabolite in certain plants.…”
mentioning
confidence: 91%
“…45 However another product, (À)-2C-methyl-D-erythrono-1,4-lactone 54 has recently been shown to be derived from DX in plants. 46 The sequence of events probably involves 2C-methyl-D-erythritol-4-phosphate 55 as an intermediate, with the later steps involving oxidation at carbon-1 and lactonisation (Scheme 17).…”
Section: Terpenoidsmentioning
confidence: 99%